Development of semi-automated guided vehicle for fertigation agriculture - Nurul Ain, Rosli; Aina Najwa, Azmi; Muhammad Ariff Hakimi, Mohd Kamal; Mohamad Rusydi, Mohamad Yasin (2021)
The design of this project is to carry the pesticide spraying system for the fertigation purpose. The system is basically a semiautomated guided vehicle controlled by Arduino Uno and guided by railway meanwhile the man power is minimized by only turned on the switch and it will move accordingly as set.